Synthesis of Heterocyclic Compounds through Multicomponent Reactions Using 6-Aminouracil as Starting Reagent - Ziarani, Ghodsi M.; Rad, Marzieh; Mohajer, Fatemeh; Sehrawat, Hitesh; Tomar, Ravi (Current Organic Chemistry, 2021)
The analogs of 6-Amino uracil are essential components due to their biological activities. The uracil is used as an important component for the synthesis of heterocyclic compounds like pyrrolo-, pyrido-, pyrimidine-pyrimido scaffolds. Herein, the application of this compound is reviewed as a precursor in the synthesis of many heterocyclic cores from 2016 to 2020.
Keywords: fused spirooxindole